2011
DOI: 10.1007/82_2011_181
|View full text |Cite
|
Sign up to set email alerts
|

Ricin and Shiga Toxins: Effects on Host Cell Signal Transduction

Abstract: Shiga toxins and ricin are potent inhibitors of protein synthesis. In addition to causing inhibition of protein synthesis, these toxins activate proinflammatory signaling cascades that may contribute to the severe diseases associated with toxin exposure. Treatment of cells with Shiga toxins and ricin have been shown to activate a number of signaling pathways including those associated with the ribotoxic stress response, Nuclear factor kappa B activation, inflammasome activation, the unfolded protein response, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 128 publications
1
39
0
Order By: Relevance
“…Once in the endoplasmic reticulum, the ricin A subunit (RTA) is liberated from RTB and is dislocated across the endoplasmic reticulum membrane into the cytoplasm, where it functions as an RNA N-glycosidase whose sole substrate is a universally conserved adenosine residue within the so-called sarcin/ricin loop of mammalian rRNA (5). Hydrolysis of the sarcin/ricin loop by RTA results in the cessation of cellular protein synthesis, activation of the ribotoxic stress response, and cell death via apoptosis (6).…”
mentioning
confidence: 99%
“…Once in the endoplasmic reticulum, the ricin A subunit (RTA) is liberated from RTB and is dislocated across the endoplasmic reticulum membrane into the cytoplasm, where it functions as an RNA N-glycosidase whose sole substrate is a universally conserved adenosine residue within the so-called sarcin/ricin loop of mammalian rRNA (5). Hydrolysis of the sarcin/ricin loop by RTA results in the cessation of cellular protein synthesis, activation of the ribotoxic stress response, and cell death via apoptosis (6).…”
mentioning
confidence: 99%
“…For example, several studies have demonstrated that intoxication with Stx activates proinflammatory and proapoptotic signaling pathways (60,61), in part through the activation of the MAPK pathway (62)(63)(64). This activation of the RSR contributes to both proinflammatory and proapoptotic signaling in cultured cells (62,63,65,66).…”
Section: Discussionmentioning
confidence: 99%
“…RTA is then dislocated (retro-translocated) across the ER membrane with the assistance of the ER-associated protein degradation system. Once in the cytoplasm, RTA triggers ribosome inactivation and programmed cell death (5). Structurally, RTA is a globular protein that can be divided into three distinct folding domains (6).…”
mentioning
confidence: 99%
“…5 Another group has reported the X-ray crystal structure of a Fab fragment in complex with cluster I (19). At the structural level, cluster I epitopes encompass ␣-helix B (residues 98 -106), ␤-strand h (residues 113-117), and the C terminus of ␣-helix D (residues 154 -156).…”
mentioning
confidence: 99%
See 1 more Smart Citation